Legal Culture of The Younger Generation in Compliance With Digital Ethics and Cyber Law: A Case Study on Social Media Use Among Students - Jaka Budiana; Alfiatur Rohmah (Universitas Sains dan Teknologi Komputer, 2025)
The rapid growth of social media use among Indonesian students poses significant challenges to compliance with digital ethics and cyber law. This study employed a qualitative case study in Jakarta and Surabaya, involving 20 high school and vocational students through interviews, online observations, and digital documentation. Findings reveal that only 20% of students demonstrated a high level of understanding of cyber law, while the majority were limited to basic terms such as cyberbullying, hoaxes, and data privacy without deeper knowledge of legal regulations. Three key factors were identified in shaping students’ digital legal culture: peer influence, family values, and school education. This research contributes by integrating a socio-legal perspective with digital media studies, highlighting that students’ legal compliance is more strongly influenced by social dynamics than by formal regulations. In practice, the findings provide a foundation for designing contextual digital legal literacy interventions through both school curricula and community-based youth approaches.